Pelatihan Hardskill dan Softskill bagi Penyandang Disabilitas di Kota Gorontalo - Rochmad Mohammad Thohir Yassin; La Ode Gusman Nasiru (Journal of Community Services on Multidisciplinary Sciences, 2025)
Hard skills and soft skills training for people with disabilities in Gorontalo City aims to improve skills and open up employment or entrepreneurship opportunities. The method used is Participatory Action Research (PAR), which is an approach whose process aims at learning in overcoming problems and meeting the practical needs of society, as well as the production of knowledge, and the process of religiousness change. The results obtained from this community service activity are hard skills training focused on introducing computer networks through Google Classroom and narrative videos on YouTube, covering material such as IP Addresses, TCP/IP, OSI 7 Layer, Routing, and DNS. Soft skills training includes communication skills, information literacy, critical thinking, and independent learning, which are relevant to increasing information accessibility, social participation, and employment opportunities.